Genetic characterization and new records of snail species of the genus Galba (Lymnaeidae) in two environments of Salta province, Northwestern Argentina - Olmos, Leandro Hipolito (2026)
The development and transmission of Fasciola hepatica, a parasitic flatworm responsible for causing fasciolosis, depend on the presence of freshwater snails belonging to the family Lymnaeidae, mainly of the genus Galba, which are obligate intermediate hosts. Although accurate identification of these snails is critical to understand disease transmission, the morphological similarities between species make taxonomic identification difficult. This study provides the first genetic characterization of freshwater snail species of the genus Galba in Salta province, Argentina. Snails were collected from two contrasting ecoregions, the Shrubland Intermontane Valleys (SIV) and the Yungas Montane Forest and Jungle (YF) and first analyzed morphologically and then molecularly using ITS-1, ITS-2, and COI markers. Two morphotypes were identified: morphotype A (elongated shell) and morphotype B (robust, globular shell). Molecular analyses revealed the presence of Galba viator in SIV and Galba neotropica in both SIV and YF, confirming the coexistence of two sympatric species in SIV. Phylogenetic analyses distinguished G. viator from the G. neotropica/G. cubensis group. These results showed the limitations of morphology for species identification and highlight the relevance of ecological plasticity of G. neotropica. This study expands the knowledge of distribution of Galba species in Argentina and provides essential baseline data to evaluate fasciolosis transmission and design control strategies.